ANALISIS SURVIVAL KARSINOMA LEHER RAHIM STADIUM LANJUT DENGAN DUA METODE TERAPI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
Radiotherapeutic treatment for advanced cervical carcinoma is unsatisfactory. A nonrandomized trial has been conducted to compare the survival rates of cervical cancer cases who received radiotherapy alone and combination of radiotherapy and chemotherapy. The subjects were all advanced cervical cancer patients who have been admitted to the Dr. Sardjito General Hospital between January 1, 1986 and December 31, 1988. The study was divided into two phases. The first phase was conducted between January 1, 1986 and December 31, 1987 involving 47 cases - 21 were treated with radiotherapy and 26 with a combination of radiochemotherapy. At the end of the 2 years follow-up period the survival rates were 38% and 58% for radiotherapy and radiochemotherapy, respectively. In the second phase 50 patients were included in the study, i.e. those admitted between January 1, 1988 and December 31, 1988 - 34 were treated with radiotherapy and 16 with chemoradiotherapy. At the end of one year follow-up period the survival rates were 62% and 69% for radiotherapy and radiochemotherapy, respectively. The differences in survival rates were not statistically significant. Key Words: cervical cancer, radiotherapy, chemoradiotherapy, survival rare